Kinetics of the histological, serological and symptomatic responses to gluten challenge in adults with coeliac disease. Issue 7 (22nd May 2012) - Leffler, Daniel; Schuppan, Detlef; Pallav, Kumar; Najarian, Robert; Goldsmith, Jeffery D; Hansen, Joshua; Kabbani, Toufic; Dennis, Melinda; Kelly, Ciarán P
Abstract : Objective: Coeliac disease is defined by gluten responsiveness, yet there are few data on gluten challenge (GC) in adults on a gluten-free diet. Lack of data regarding the kinetics of responses to gluten is a limitation in clinical practice and research when GC is performed. Design: 20 adults with biopsy-proven coeliac disease participated. The study included two run-in visits followed by a 14-day GC at a randomly assigned dose of 3 or 7.5 g of gluten/day. Study visits occurred 3, 7, 14 and 28 days after starting GC. Duodenal biopsy was performed during the run-in and at days 3 and 14 of GC. Villous height to crypt depth ratio (Vh:Cd) and intraepithelial lymphocyte (IEL) count/100 enterocytes were measured by two pathologists. Antibodies to tissue transglutaminase and deamidated gliadin peptides, lactulose to mannitol ratio (LAMA) and symptoms were assessed at each visit. Results: Significant reduction in Vh:Cd (2.2–1.1, p<0.001) and increase in IELs (32.6–51.8, p<0.001) were seen from baseline to day 14. Antibody titres increased slightly from baseline to day 14 of GC but markedly by day 28. LAMA did not change significantly. Gastrointestinal symptoms increased significantly by day 3 and returned to baseline by day 28. No differences were seen between the two gluten doses. Conclusions: 14 day GC at ≥3 g of gluten/day induces histological and serological changes in the majority of adults with coeliac disease. These data permit accurate design of clinical trials and indicate that many individuals will meet coeliac diagnostic criteria after a 2-week GC. Clinical Trials Registration Number: http://clinicaltrials.gov # NCT00931892 .